Предмет: Алгебра, автор: romaklimov2006

помогите, пожалуйста! срочно!!!!​

Приложения:

Ответы

Автор ответа: MatemaT123
1

Ответ:

\frac{y+x}{y-x}

Объяснение:

(x^{-1}-y^{-1})^{-2}:(x^{-2}-y^{-2})^{-1}=\frac{1}{(\frac{1}{x}-\frac{1}{y})^{2}}:\frac{1}{\frac{1}{x^{2}}-\frac{1}{y^{2}}}=\frac{\frac{1}{x^{2}}-\frac{1}{y^{2}}}{(\frac{1}{x}-\frac{1}{y})^{2}}=\frac{\frac{y^{2}-x^{2}}{x^{2}y^{2}}}{(\frac{1}{x}-\frac{1}{y})^{2}}=

\frac{y^{2}-x^{2}}{(xy)^{2} \cdot (\frac{1}{x}-\frac{1}{y})^{2}}=\frac{y^{2}-x^{2}}{(xy \cdot (\frac{1}{x}-\frac{1}{y}))^{2}}=\frac{y^{2}-x^{2}}{(y-x)^{2}}=\frac{(y-x)(y+x)}{(y-x)(y-x)}=\frac{y+x}{y-x};

Похожие вопросы